Genomic risk prediction of cardiovascular diseases among type 2 diabetes patients in the UK Biobank - Ye, Yixuan; Hu, Jiaqi; Pang, Fuyuan; Cui, Can; Zhao, Hongyu (Frontiers in Bioinformatics, 2024)
Background: Polygenic risk score (PRS) has proved useful in predicting the risk of cardiovascular diseases (CVD) based on the genotypes of an individual, but most analyses have focused on disease onset in the general population. The usefulness of PRS to predict CVD risk among type 2 diabetes (T2D) patients remains unclear.We built a meta-PRSCVD upon the candidate PRSs developed from state-of-the-art PRS methods for three CVD subtypes of significant importance: coronary artery disease (CAD), ischemic stroke (IS), and heart failure (HF). To evaluate the prediction performance of the meta-PRSCVD, we restricted our analysis to 21,092 white British T2D patients in the UK Biobank, among which 4,015 had CVD events.Results: Results showed that the meta-PRSCVD was significantly associated with CVD risk with a hazard ratio per standard deviation increase of 1.28 (95% CI: 1.23-1.33). The meta-PRSCVD alone predicted the CVD incidence with an area under the receiver operating characteristic curve (AUC) of 0.57 (95% CI: 0.54-0.59). When restricted to the early-onset patients (onset age <= 55), the AUC was further increased to 0.61 (95% CI 0.56-0.67).Our results highlight the potential role of genomic screening for secondary preventions of CVD among T2D patients, especially among early-onset patients.